2022
DOI: 10.1128/jvi.00826-22
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Viral Hijacking of CRL4 Ubiquitin Ligase through Structural Analysis of the pUL145-DDB1 Complex

Abstract: Many different viruses modulate the protein machinery required for ubiquitination to enhance viral fitness. Specifically, several viruses hijack the cullin-RING ligase CRL4 DDB1 to degrade host resistance factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…Our biochemical analysis indicated that E27 replaces the endogenous DCAF1 substrate receptor on DDB1. This is in agreement with recent results demonstrating that H‐box peptides of the vDCAFs UL145 and HBx exhibit significantly higher DDB1‐binding affinities than the corresponding H‐box peptides derived from endogenous DCAF1 and DDB2 receptors (Wick et al , 2022 ). Accordingly, it is tempting to speculate that vDCAFs, in addition to marking antiviral substrates for degradation, might block a plethora of cellular DCAF‐dependent ubiquitylation processes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our biochemical analysis indicated that E27 replaces the endogenous DCAF1 substrate receptor on DDB1. This is in agreement with recent results demonstrating that H‐box peptides of the vDCAFs UL145 and HBx exhibit significantly higher DDB1‐binding affinities than the corresponding H‐box peptides derived from endogenous DCAF1 and DDB2 receptors (Wick et al , 2022 ). Accordingly, it is tempting to speculate that vDCAFs, in addition to marking antiviral substrates for degradation, might block a plethora of cellular DCAF‐dependent ubiquitylation processes.…”
Section: Discussionsupporting
confidence: 93%
“…Sequence alignments from previous and from our present study indicate the presence of an H-box motif in the N terminus of UL145 (residues [25][26][27][28][29][30][31][32][33][34][35][36]Fig 4D), suggesting that this UL145 region is positioned similarly in the DDB1-binding cleft as endogenous DCAF substrate receptors and the C-terminal half of E27 helix a8. Indeed, site-directed mutagenesis of several putative H-box residues in UL145 abrogated DDB1 interaction in coimmunoprecipitation experiments , and a crystal structure of the UL145 H-box peptide in complex with DDB1 very recently supplied the ultimate proof of this hypothesis (Wick et al, 2022). However, future structural studies are necessary to clarify how the whole of UL145 integrates into CRL4, in order to pinpoint additional DDB1-interacting motifs and to decipher the mechanisms of STAT2 recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Our biochemical analysis indicated that E27 replaces the endogenous DCAF1 substrate receptor on DDB1. This is in agreement with recent results demonstrating that H-box peptides of the vDCAFs UL145 and HBx exhibit significantly higher DDB1-binding affinities than the corresponding H-box peptides derived from endogenous DCAF1 and DDB2 receptors (Wick et al, 2022). Accordingly, it is tempting to speculate that vDCAFs, in addition to marking antiviral substrates for degradation, might block a plethora of cellular DCAF-dependent ubiquitylation processes.…”
Section: Discussionsupporting
confidence: 93%
“…4D), suggesting that this UL145 region is positioned similarly in the DDB1-binding cleft as endogenous DCAF substrate receptors and the C-terminal half of E27 helix α8. Indeed, site-directed mutagenesis of several putative H-box residues in UL145 abrogated DDB1 interaction in co-immunoprecipitation experiments (Le-Trilling et al, 2020), and a crystal structure of the UL145 H-box peptide in complex with DDB1 very recently supplied the ultimate proof of this hypothesis (Wick et al, 2022). However, future structural studies are necessary to clarify how the whole of UL145 integrates into CRL4, in order to pinpoint additional DDB1-interacting motifs, and to decipher the mechanisms of STAT2 recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…This approach takes advantage of the fact that various types of viruses interact extensively with many CRL components, which allows them to manipulate specific host cell proteins for their own benefit. ,,, For example, CRL4 DCAF1 was initially found to be hijacked by the HIV-1 accessory viral protein R (Vpr), leading to its alternative name as Vpr-binding protein (VprBP). In this context, Vpr targets host cell proteins including uracil DNA glycosylase 2 (UDG2), endoribonuclease Dicer, and deacetylase sirtuin 7 (SIRT7) for proteasomal degradation, thereby prolonging HIV-1 replication. , Additionally, Vpr can also hijack the HECT-type E3 ligase UBR5 (also referred to as EDD)–DYRK2–DDB1 DCAF1 complex, leading to the degradation of host cell proteins CP110 and katanin ((Figure A, B). Likewise, the accessory viral protein X (Vpx) of HIV-2 and its related simian immunodeficiency virus (SIV) was found to hijack CRL4 DCAF1 for proteasomal degradation of the host cell protein SAMHD1. , In this context, Cullgen, a pure play in TPD, successfully identified ligands that bind to the virally hijacked DDB1 and incorporated them into the design of PROTACs (see A17 and A18 in Figure C). , To date, structural studies have provided valuable insights into the interactions between these viral proteins and the CRL components. Careful examination of these PPIs may guide the development of small-molecule ligands for CRL components, and we expect to see more of this practice in the future.…”
Section: Perspectivesmentioning
confidence: 99%